Toward consumer-focused food policies: a toolbox for encouraging the protein transition - Hans Dagevos; Marleen C. Onwezen (Sustainability: Science, Practice, & Policy)
In transitioning toward consuming more sustainable diets, it is of great importance to eat less animal-based foods. Particularly shifting to diets lower in meat is key. For several decades, numerous scholars and authoritative organizations have advocated for such a change that is less harmful to human and planetary health. Yet the large body of scientific evidence and the urgent calls for action have been largely neglected in food policymaking despite the increasing impact of climate change and escalating healthcare costs. A first and relatively minor break with this willful ignorance can be observed in the Netherlands, where the Ministry of Agriculture, Nature, and Food Quality has communicated the need for rebalancing the consumption ratio between plant-based and animal-based proteins by 2030. This innovative policy statement on modifying food-consumption patterns is taken as a starting point. In anticipation of further steps in this direction, this article presents a suite of policy instruments and strategies to give substance to demand-side protein policies that are conducive to moderating consumers’ (over-)abundant intake of meat. This overview of policy measures includes conventional and controversial ones, taking the Nuffield intervention ladder as its framework. The novel policy toolbox introduced in this study intends to help muster courage for the development and implementation of consumer-targeted policy interventions to move away from meat-intensive diets.